2020
DOI: 10.15689/ap.2020.1902.02
|View full text |Cite
|
Sign up to set email alerts
|

Vitimização e Psicopatia em Autores de Violência Sexual contra Crianças e Adolescentes

Abstract: RESUMOO objetivo do estudo foi investigar a vitimização em autores de violência sexual (AVS) contra crianças e adolescentes, assim como sua relação com traços de psicopatia. Participaram 30 reeducandos cumprindo pena em regime fechado por crimes sexuais contra crianças e adolescentes, que foram divididos em dois grupos: G1, AVS considerados psicopatas (PCL-R≥30); G2, AVS não psicopatas (PCL-R<30).Os instrumentos utilizados no estudo foram: Psychopathy Checklist Revised (PCL-R) e Juvenile Victimization Question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…The results indicate that the profile of the CSA perpetrators outlined in this sample comprises non-Caucasian adult men with a low educational level who profess the evangelical religion. Part of these results confirms the findings from a previous study addressing men who committed sexual aggression (Teixeira, Resende & Perissinotto, 2020), which reported the same The same study comparing the control group showed that CSA perpetrators would be four times more likely to obtain higher scores. Levenson, Willis, and Prescott (2014) also identified low levels of CSA in perpetrators who reported that they had not experienced any ACE and higher levels of ACE-Score in approximately half of the sample (CSA perpetrators), with a total mean of 3.5, lower to that found in this study.…”
Section: Discussionsupporting
confidence: 88%
“…The results indicate that the profile of the CSA perpetrators outlined in this sample comprises non-Caucasian adult men with a low educational level who profess the evangelical religion. Part of these results confirms the findings from a previous study addressing men who committed sexual aggression (Teixeira, Resende & Perissinotto, 2020), which reported the same The same study comparing the control group showed that CSA perpetrators would be four times more likely to obtain higher scores. Levenson, Willis, and Prescott (2014) also identified low levels of CSA in perpetrators who reported that they had not experienced any ACE and higher levels of ACE-Score in approximately half of the sample (CSA perpetrators), with a total mean of 3.5, lower to that found in this study.…”
Section: Discussionsupporting
confidence: 88%
“…A partir dos resultados obtidos, foi possível identificar que o perfil de AASCA delineado nesta amostra é composto por homens adultos, não brancos, com baixa escolaridade e que professam a religião evangélica. Parte desses dados confirmam achados de estudo anterior com homens que praticaram agressão sexual (Teixeira et al, 2020) nenhuma EAI e níveis mais altos de ACE-Score em aproximadamente metade da amostra de AASCA, com uma média total de 3.5, inferior à encontrada neste estudo.…”
Section: Discussionunclassified
“…17 Given this, it is notorious the misuse of power of the responsible for the crime, who feel on the right to perpetrate sexual violence against a child. 11, 18,19 Taking into account that, in such cases, the legislation concerns the right to terminate pregnancy. 20 Therefore, it is essential that population know about prevention and orientation measures in cases of child sexual abuse, such as: calling public authorities, dial 100 (violation of human rights), dial 190 (civil police), taking the victim to the nearest emergency department, taking preventive cares against STIs, knowing about procedures related to pregnancy stemming from rape and treatment of injuries, laboratory tests, referral to the Guardianship Council, refer the child to social assistance.…”
mentioning
confidence: 99%